From the nightlife to the school day: a survey of informal music learning experiences and perspectives among music educators - Flory, Wilson Reese (Kansas State University, 2014)
The purpose of this study was to determine if music educators who have had experiences with informal music are more likely to employ informal learning within their classroom. Secondary research objectives included a comparison of survey results against specific demographics of the survey participants, an examination of the types of informal learning that the participants experienced and facilitated, and a look at the perceived barriers and benefits of informal music learning from the viewpoints of the participants. Participants (N=25) were practicing music educators pursuing graduate music studies. The participants were enrolled in a summer Master of Music program at a university in the Midwest. Data was collected by employing a pen and paper survey that provided a demographic description and informal music learning questionnaire. The participants were asked to indicate the frequency of participation in informal music activities prior to becoming a music educator. They further reported what informal music learning activities they facilitate within their school music curriculum. Finally, the participants responded to two short answer questions where they identified barriers and benefits they perceive with the implementation of informal music practices within their music programs. Results from a Pearson correlation showed a moderately strong relationship (p = 0.43) between participants who had informal music experiences (E) and who employed informal music learning within their music curriculum (C). There were no significant differences observed in the results between participants of different gender or school division. Of the short answer responses cataloged, participants cited a lack of experience with informal music and difficulty of connecting informal music learning to the formal music curriculum as the barriers to employing informal music learning in the classroom. The participants discussed the increase in student motivation, expanding musicality, and real-world relevance as the benefits of informal music learning. Knowledge gained from this study may be useful to individuals facilitating informal music learning within music education programs at the primary, secondary, or collegiate levels.
Keywords: Informal learning; Informal music; Music education; Arts advocacy; Music curriculum; Relevance in music education; Music (0413); Music Education (0522)